The modern dwelling - Norton, Ellen Elizabeth (My University, 1896)
Introduction: About forty years ago there appeared in one of our popular magazines an article entitled, “Hints for House Builders,” in which the following statement was made: “Square boxes, small and large are springing up in every direction, constructed without any attempt at proportion, or the slightest apparent desire to make them agreeable objects in the landscape. These tell their tale simply and unceremoniously, they demonstrate that the capacity for enjoyment and the appreciation of what is really desirable in life is wanting. Back of these bare, bold, white cubes, tells its monotonous story of a youth passed with little or no cultivation of the higher natural perceptions, and a system of education in which the study of the beautiful, in its most simple elements, is neglected and apparently despised.” What was true then is true to a certain extent today. It is only in the most cultured communities that the people have succeeded in getting away from this utilitarian idea. But the history of architecture carries the comforting assurance that structures can be both beautiful and useful.
Citation: Norton, Ellen Elizabeth. The modern dwelling. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Popular magazines; Architecture; History; Theses; Manuscripts (documents)